Pseudomonas avellanae causing European hazelnut decline in Serbia - POPOVIĆ MILOVANOVIĆ Tatjana; LORETI, Stefania; MILOVANOVIĆ Predrag; JELUŠIĆ Aleksandra; ILIČIĆ Renata; CESARI , Erica; SCORTICHINI , Marco (Phytopathologia Mediterranea, 2026)
The plant pathogenic bacterium Pseudomonas avellanae, the causal agent of decline and dieback of hazelnut (Corylus avellana), affects vascular tissues of host trees and leads to the rapid wilting of leaves. Severe damage to hazelnut orchards has been reported in northern Greece and central Italy. In 2024, hazelnut trees (cv. Tonda di Giffoni) showed symptoms of rapid leaf wilting and brown discolouration of vascular tissues in the branches. Isolations resulted in convex, levan-positive, mucoid, cream-whitish bacterial colonies on Nutrient agar (plus 5% sucrose), which LOPAT results (+—+) identified the bacteria as Pseudomonas syringae group Ia. Preliminary identification of isolates was achieved using specific conventional PCR (cPCR) for P. avellanae. Further genetic identification and characterization was carried out using multilocus sequence analysis (MLSA) using five housekeeping genes (gyrB-gapA-gltA-rpoD-recG). Repetitive ERIC-PCR fingerprinting of two Serbian isolates from hazelnut, 13 Italian, and one Greek isolate of P. avellanae revealed three distinct molecular patterns. The Serbian isolates clustered with the Italian strains, while the Greek strain formed a more distinct group. Pathogenicity assessments, carried out by inoculating 1-year-old hazelnut plants (Tonda di Giffoni), resulted in the development of necrosis at the inoculation sites 10 d post-inoculation, which reached lengths 15-20 cm longitudinally along the stems within 2 months. The inoculated bacterium was re-isolated from the stems of inoculated plants. This study highlights the emerging threat of P. avellanae to hazelnut production, with significant implications for the European hazelnut industry. Spread of this pathogen across regions, and the potential impacts on orchard health, emphasize the need for enhanced monitoring and disease management strategies.